SQL for Dummies - Taylor, Allen G (John Wiley & Sons, Incorporated, 2010)
Learn SQL the fun and easy way - no programmingexperience needed! SQL For Dummies, 7th Edition, shows programmers and webdevelopers how to use SQL to build relational databases and getvaluable information from them. This book covers the core featuresof the SQL language. Topics covered include how to use SQL tostructure a DBMS and implement a database design; secure adatabase; and retrieve information from a database. This editionwill be revised to reflect the new enhancements ofSQL/XML:2008. The latest update of the perennial bestselling SQL ForDummies, which has sold more than 210,000 units in sixeditions.SQL is the most popular database language in the worldCovers creating, accessing, manipulating, maintaining, andstoring information in relational database management systems(DBMS) such as Access, Oracle, SQL Server, and MySQL.Includes new content on using SQL with XML to power data-drivenweb sites and using SQL with Access 2010 Whether you're daunted by database development or a system adminstar, SQL For Dummies, 7th Dummies will have you workingyour web site in no time at all.